Spiritual Healing Practices Among Rural Postpartum Thai Women - Prangthip Thasanoh Elter (2018)
© 2014, © The Author(s) 2014. Purpose: Postpartum Thai women follow family instructions to recover health at home. This study explores first-time mothers’ experiences with postpartum family practices. This article presents the experiences with spiritual healing, one of the three essences of Thai traditional medicine. Design: An interpretive phenomenological study was conducted in rural Thailand. Participants were 16 pregnant women purposively recruited. Data were collected using in-depth interviews, participant observations, and a demographic record and were analyzed using thematic and exemplar analysis. Results: The women adhered to practices and rituals related to beliefs about three essences (the body, mind–heart, and energy). Spiritual healing works on mind–heart essences. Conclusion: A new mother healed her spirit through traditional postpartum practices. The findings provide an understanding of the practices within the context of rural Thai women’s families. This information can guide future implementation of postpartum care, with awareness of and respect for cultural practices in fulfilling spiritual needs.